Nasab dalam Perspektif Tafsir Ahkam - M Jamil (AHKAM : Jurnal Ilmu Syariah, 2016)
Family relationship for someone is something very important. Due to this relation, people would have family relation to whom they are connected. The importance of nasab discussion because it relates someone to a lot of matters, such as inheritance, guardian, and equality (kafâ’ah) of husband and wife before marriage. The fiqh scholars and commentators disagree with the meaning of nasab. Many Scholars say that nasab is the relationship between a man and his child related to legal marriage. Hanafiyah states that nasab is the relationship between a man and his child due to genetic relationship. The logical consequence of this difference is in inheritance. Many scholars assert that inheritance is only connected to legitimate family relationship while Hanafiyah tend to say that inheritance is related to blood relations.DOI: 10.15408/ajis.v16i1.2902